Entrepreneurship and survival dynamics of immigrants to the US and their descendants - Dimitris Georgarakos; Konstantinos Tatsiramos (Institute for the Study of Labor (IZA), 2007)
Many studies have explored the determinants of entering into entrepreneurship and the differences in self-employment rates across racial and ethnic groups. However, very little is known about the survival in entrepreneurship of immigrants to the U.S. and their descendants. Employing data from the Survey of Income and Program Participation, we find a lower survival probability in entrepreneurship for Mexican and other Hispanic immigrants, which does not carry on to their U.S.-born descendants. We also find that these two immigrant groups tend to enter entrepreneurship from unemployment or inactivity and they are more likely to exit towards employment in the wage sector, suggesting that entrepreneurship represents for them an intermediate step from non-employment to paid employment.
urn:nbn:de:101:1-20080401387
Keywords: 330; Unternehmer; Selbstständige; Unternehmensgründung; Migranten; Hispano-Amerikaner; Ethnische Gruppe; Unternehmensentwicklung; USA